Inequality and access to services for remote populations: An Australian case study. (December 2022) - Rottemberg, Julieta; Ghasri, Milad; Grzybowska, Hanna; Dockery, Alfred M.; Waller, S. Travis
Abstract: Almost half of the world population lives in rural and remote areas facing more challenging and hazardous life conditions than the rest of the population. This paper and proposed method contribute to addressing an apparent gap in modelling travel-related decisions of rural and remote populations to enhance equitable access to basic amenities (e.g., education, health services, retail) for these populations. The application of these models is highly relevant for planning and policy purposes in remote communities. This paper uses data obtained from a mobility survey of remote Aboriginal communities in Central Australia to estimate purpose-specific destination choice models for access to basic services. The analysis is based on stated preference data to measure the attractiveness of destinations. Then, the models are used to analyse the impact of increasing the number of services provided in the remote communities. A better understanding of the impact of local development on travel patterns in remote communities is provided by analysing three aspects: attracted trips to the destinations, reduction of distance travelled by travellers in all the communities and improved equity in the distribution of travel distance among the communities. The case study illustrates the method successfully determines the most relevant parameters in the decisions of the surveyed individuals and determines potential destinations for local development, with the final objective of contributing to the alleviation of accessibility and inclusion problems in remote areas.